From collaborative writing to reading comprehension : a case study on focus on form through collaborative dialogue as a means to enhance reading comprehension in English - Seba, Rosângela Guimarães (2008)
Recent research in second language acquisition has acknowledged the importance of verbal interaction in the development of competence in the target language. Grounded in sociocultural theoretical framework (Vygostky, 1978) and based on the works of Swain and her associates (1985-2006), the present study aimed to investigate the effectiveness of collaborative dialogue with a conscious and spontaneous focus on form for the improvement of reading comprehension skills in English. According to Swain (2000), collaborative dialogue is knowledge-building dialogue (with others and/or with the self) which construes language not only as communication, but as a cognitive tool. It refers to spontaneous learners talk about language in their attempt to solve a linguistic problem as they work collaboratively in small groups. Two voluntary EFL adult learners of an English for Academic Purposes (EAP) course from a university in the State of Espírito Santo, Brazil with an intermediate level of English proficiency participated in the research. Data were collected over a period of four regular classes (2h each), in which participants worked collaboratively on producing and reformulating tasks. Microgenetic qualitative analysis of the collaborative dialogue between the participants provided evidence of the focus of learners negotiated interaction, and the writing and reading strategies they used while working on tasks. The findings confirm the postulates of Vygotsky s (1978) sociocultural theory about human cognitive development through social interaction, and corroborate Swain s (1985) Comprehensible Output Hypothesis which claims that the act of producing language (speaking and writing) may be a source of language learning. There seems to be evidence to suggest that collaborative dialogue with learner-generated attention to form and lexis may lead learners to a deeper understanding of their production, and to greater awareness of writing and reading strategies. Thus, the current research study seems to indicate that, at least in certain teaching and learning contexts collaborative dialogue with spontaneous focus on form through writing tasks in dyads or in small groups may facilitate the process of reading comprehension.